SISTEM INFORMASI INVENTORY BERBASIS WEB DENGAN MENGGUNAKAN MODEL WATERFALL - Adwiya, Rabiatul Adwiya (JTIK (Jurnal Teknik Informatika Kaputama), 2023)
The development of technology is increasing, and the demand for clear and accurate data information is increasing. Computers are an important tool to help companies complete work in their respective fields. One of the successes of a company is being able to manage the company's inventory of goods, inventory itself is the inventory of goods owned to predict the satisfaction of consumer needs, how to meet needs. The existence of this information system can improve company performance by speeding up all processes. All systems in the company become an integrated system with one database, so sharing data becomes easier across several departments. So far, the recording of inventory at PT Rezeki Kencana is still done manually, such as only recording in a book. This manual recording causes several problems such as taking a long time to find history data because you have to check page by page from the book to find an item. Therefore, the author will design a web-based inventory system whose purpose is to facilitate inventory management. In this research, the data collection methods used by the author are observation, interview, and literature study and use the waterfall method as the software development method used by the author. From this research, the author hopes that the creation of an inventory system at PT Rezeki Kencana will make it easier for goods managers to input goods, process stock items, process goods transactions, and report goods data.